Analysis Of Waburi Park Tourism Destination Development Case Study In The New Gaya Village Of District Lapandewa South Buton District - Majeyono; Rifdan; Andi Muhammad Rivai; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2025)
This study aims to examine the development of Waburi Park as a tourist destination using a holistic approach that considers social, economic, cultural, and environmental aspects. The main focus is the identification of key factors related to marketing and promotion, accessibility, tourism areas, and human resources. A descriptive method with a qualitative approach was employed, using in-depth interviews with stakeholders. Case studies were conducted on selected tourist destinations chosen for their natural and cultural potential. The findings indicate that effective promotion, particularly through digital platforms, has a significant impact on increasing tourist visits. Moreover, accessibility—including transportation infrastructure and connectivity has proven to be a crucial factor in enabling tourists to reach destinations. Proper management of tourism areas, including the development of facilities and environmental sustainability, also contributes to enhancing the tourist experience. In addition, the competence of human resources in the tourism sector, especially in service delivery and communication skills, strongly influences the quality of services received by visitors. This study recommends stronger synergy among the government, industry stakeholders, and local communities to improve promotion, accessibility, and tourism area management, as well as to strengthen human resource capacity in order to achieve sustainable tourism development.